Morphology and molecular analysis of the Brittle star (Ophiocoma scolopendrina) in the coastal waters of Aceh Besar, Indonesia - ASRI MURSAWAL; SRI WAHYUNI; NI KADEK DITA CAHYANI; M. ALI SARONG; IRWAN EFFENDI; RONAL KURNIAWAN (Society for Indonesian Biodiversity, 2026)
Abstract. Mursawal A, Wahyuni S, Cahyani NKD, Sarong MA, Effendi I, Kurniawan R. 2026. Morphology and molecular analysis of the Brittle star (Ophiocoma scolopendrina) in the coastal waters of Aceh Besar, Indonesia. Biodiversitas 27 (5): d270512. https://doi.org/10.13057/biodiv/d270512. Brittle stars (Ophiuroidea) are important benthic organisms that play a key role in ecological processes within coastal and coral reef ecosystems. However, information on the combined morphological and genetic characteristics of brittle star populations in the coastal waters of Aceh Besar, Indonesia, remains limited. This study aimed to examine morphological characteristics and genetic diversity of Ophiocoma scolopendrina from three coastal sites in Aceh Besar using a combined morpho-molecular approach. Specimens were collected from Lhok Mee (LM), Lhok Redeup (LR), and Lhok Seudu (LS) using purposive sampling of intact adult individuals suitable for morphological and molecular analyses. A total of 96 specimens were analyzed. Morphological identification was based on standard diagnostic characters, while molecular analysis targeted partial mitochondrial 16S rRNA gene sequences ( 430 bp). Genetic diversity indices, including haplotype diversity (Hd) and nucleotide diversity (π), were calculated, and population structure was assessed using pairwise FST and Analysis of Molecular Variance (AMOVA). Results showed consistent morphological traits across locations with minor variation in coloration. Genetic analysis revealed high haplotype diversity (Hd = 0.867-0.962) and low nucleotide diversity (π = 0.010-0.016). Pairwise FST values were low (0.002-0.016), and AMOVA indicated weak and non-significant genetic differentiation among populations (FST = 0.012; P = 0.088). These findings suggest weak mitochondrial population structuring among sites. However, results should be interpreted cautiously due to the use of a single mitochondrial marker and purposive sampling design. This study provides baseline data on morphology and genetic diversity of O. scolopendrina in Aceh Besar, supporting biodiversity monitoring research in tropical coastal ecosystems.